The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/eat.20913
|View full text |Cite
|
Sign up to set email alerts
|

Perception of control during episodes of eating: Relationships with quality of life and eating psychopathology

Abstract: Objective: Experience of loss of control (LOC) during eating is an important indicator of pathology, although this concept has not received a great deal of research attention. The present study explores how quality of life (QoL) is related to LOC during eating.Method: Three hundred and thirtynine female university students completed measures of eating pathology, general psychiatric symptomatology, and QoL. They were subsequently categorized according to the degree of LOC experienced during eating into one of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 25 publications
(11 reference statements)
7
33
0
Order By: Relevance
“…[6][7][8]10 AN had the lowest BMI and BN had the highest BMI of the groups. Previous research has generally shown a positive association between OBEs and BMI, 7,16,49 likely attributable to higher caloric intake and retention from overeating episodes. Keel et al's finding of increased impulsivity in the BN group relative to the SBN group fuelled debate about whether impulsivity is a central feature of BN or an epiphenomenon; we did not reproduce this difference in impulsivity between SBN and BN.…”
Section: Descriptive Statisticsmentioning
confidence: 95%
See 1 more Smart Citation
“…[6][7][8]10 AN had the lowest BMI and BN had the highest BMI of the groups. Previous research has generally shown a positive association between OBEs and BMI, 7,16,49 likely attributable to higher caloric intake and retention from overeating episodes. Keel et al's finding of increased impulsivity in the BN group relative to the SBN group fuelled debate about whether impulsivity is a central feature of BN or an epiphenomenon; we did not reproduce this difference in impulsivity between SBN and BN.…”
Section: Descriptive Statisticsmentioning
confidence: 95%
“…This study's findings have implications for treatment. Given the pathology and impairment associated with subjective binge eating, 7,9,10,12,14,16,17,49 it would seem important to target more specifically, subjective binge eating within existing cognitivebehavioral interventions. Research is mixed, with some studies finding that cognitive-behavioral therapy (CBT) is slower or less effective at reducing subjective compared to objective binge eating, [51][52][53] but others showing a similar response.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…The sense of "loss of control" (LOC) 7 over eating has been suggested to be the most important feature of the binge-eating episodes definitive of bulimia nervosa (BN), binge eating disorder, and the binge-eating/purging subtype of anorexia nervosa (AN) (1,(2)(3)(4)(5). Subjective LOC over eating also prospectively predicts weight gain (6,7) and the development of objectively large binge-eating episodes (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is ample evidence of the frequent occurrence of SBEs with or without concurrent OBEs in community samples [3-5] and in clinical samples [6-10]. For example, in a recent interview-based study with female college students, 11.8% of the participants reported the presence of SBEs, 15.3% had OBEs and 13.6% described both, OBEs and SBEs [4]. Another investigation in 339 adult women with eating disorders (ED) features recruited from the general community reported current prevalence of 58.4% for weekly SBEs and of 41.5% for weekly OBEs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also reported that individuals with BED and BN identify binge episodes more by feelings of LOC than by the amount of food eaten, although those with BN tend to report larger binge episodes [15,18-20]. Because of the difficulty in operationalising the concept of a “large amount”, it has been proposed that LOC should be the defining feature of a binge eating episode [4,14,15,21,22]. …”
Section: Introductionmentioning
confidence: 99%